2014
DOI: 10.1128/mcb.00075-14
|View full text |Cite
|
Sign up to set email alerts
|

Tsc2 Is a Molecular Checkpoint Controlling Osteoblast Development and Glucose Homeostasis

Abstract: g Insulin signaling in osteoblasts regulates global energy balance by stimulating the production of osteocalcin, a bone-derived protein that promotes insulin production and action. To identify the signaling pathways in osteoblasts that mediate insulin's effects on bone and energy metabolism, we examined the function of the tuberous sclerosis 2 (Tsc2) protein, a key target important in coordinating nutrient signaling. Here, we show that loss of Tsc2 in osteoblasts constitutively activates mTOR and destabilizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 57 publications
(84 reference statements)
3
57
0
Order By: Relevance
“…Deletion of either Tsc1 in preosteoblasts using Osx:cre (ΔTsc1 mice [57]) or Tsc2 in mature osteoblasts using Ocn:cre (ΔTsc2 mice [58]), results in constitutive activation of mTORC1. In both models, hyperactivation of mTORC1 leads to an increase in postnatal bone mass that was evident in cortical and trabecular regions of the long bones and calvarial bones of the skull.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of either Tsc1 in preosteoblasts using Osx:cre (ΔTsc1 mice [57]) or Tsc2 in mature osteoblasts using Ocn:cre (ΔTsc2 mice [58]), results in constitutive activation of mTORC1. In both models, hyperactivation of mTORC1 leads to an increase in postnatal bone mass that was evident in cortical and trabecular regions of the long bones and calvarial bones of the skull.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to gain-of-function mouse models, the evidence from loss-of-function studies suggests that mTORC1 may play a role in promoting osteoblast differentiation. Mice with the hom deletion of mTOR in mature osteoblasts (Ocn:cre ΔmTOR) demonstrate reduced tibial trabecular bone volume and trabecular number (58). This phenotype can be attributed to impaired mTORC1 function since mice with homozygous deletion of Rictor, an essential component of mTORC2, in mature osteoblasts have no tibial bone phenotype (60).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using rapamycin, an mTORC1 inhibitor, have showed both positive [911] and negative [1215] effects on osteogenesis in vitro . Some recent reports demonstrated the important roles of mTOR signaling in skeletal development [1618] . However, despite the high prevalence of bone lesions in TSC patient, the underlying bone lesion mechanism is largely unknown, which is mainly due to the lack of appropriate animal models of TSC bone lesions.…”
mentioning
confidence: 99%
“…Interestingly, mutant bones had not only increased mass but also increased tissue mineral density (Xiaoxi Wei and Fei Liu, unpublished). Interestingly, TSC2 deletion in mature osteoblasts also leads to increased calvaria thickness [16] . However, the disorganized bone structure was reported in that study, which is clearly different from the highly mineralized bone in our model.…”
mentioning
confidence: 99%
“…This notion was supported by a study from the Clemens’ group showing that mice harboring osteoblast specific ablation of Tsc2 have improved glucose handling with increased levels of insulin and undercarboxylated osteocalcin at 1 week of age. However, with age, these mutant mice developed opposite metabolic phenotypes due to chronic elevations in undercarboxylated osteocalcin that down-regulating Gprc6a expression and therefore desensitizing osteocalcin signaling in pancreatic β-cells [133]. Taken together, these genetic and pharmacological studies reveal the pivotal role that osteocalcin plays in the development of metabolic diseases and suggests that harnessing osteocalcin signaling may be of therapeutic use for metabolic diseases.…”
Section: Pathological Relevance and Therapeutic Implicationsmentioning
confidence: 99%